2021
DOI: 10.1039/d0ra09561c
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular systems for dermal and transdermal drug delivery

Abstract: Dermal/transdermal drug delivery continues to grow in importance as a means of enhancing treatment activity while reducing toxicity by avoiding the systemic absorption of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 100 publications
0
33
0
Order By: Relevance
“…1) (Sarhan et al 2020;Wu et al 2019). Edge Activator has a 25% usage limit on Transfersomes (Richard, Cassel, and Blanzat 2020). Thus, vesicle size is reduced as a result of increased solubility.…”
Section: Transfersomementioning
confidence: 99%
“…1) (Sarhan et al 2020;Wu et al 2019). Edge Activator has a 25% usage limit on Transfersomes (Richard, Cassel, and Blanzat 2020). Thus, vesicle size is reduced as a result of increased solubility.…”
Section: Transfersomementioning
confidence: 99%
“…Thus, some prospective strategies, including both chemical and physical methods, have been investigated in order to overcome the SC barrier [8,9,14,24,27]. The methods utilized to modify the barrier properties of the SC can be classified as chemical and physical methods, as summarized in Figure 3 [14,28]. Prausnitz and Langer described three generations of TDD systems in a paper published in 2008 [8].…”
Section: Techniques For Enhancement Of Skin Permeabilisationmentioning
confidence: 99%
“…The characteristics of vesicles, rather than the physicochemical properties of drug molecules, control the clearance and tissue distribution profile of a drug when delivered by such a delivery system [81]. Based on the physicochemical characteristics of the drug, it can be encapsulated in the internal cavity or be included in the bilayer [28]. Hence, vesicles can load hydrophilic, lipophilic, and amphiphilic drugs to achieve transdermal delivery [10].…”
Section: Surfactantsmentioning
confidence: 99%
“…Understanding the physicochemical properties of transdermal DDSs, such as particle size, fluidity, rigidity, and carrier morphology, is important for determining the possibility of skin penetration. It has been reported that rigid liposomes can prolong transdermal delivery as they deposit the drugs on the skin surface, whereas fluid vesicles can be considered for transdermal diffusion . Understanding these basic properties and behavior is crucial for optimizing the design of a carrier for a particular purpose.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rigid liposomes can prolong transdermal delivery as they deposit the drugs on the skin surface, whereas fluid vesicles can be considered for transdermal diffusion. 25 Understanding these basic properties and behavior is crucial for optimizing the design of a carrier for a particular purpose.…”
Section: ■ Introductionmentioning
confidence: 99%